The Burda Poem And The Research, Writings And Oppositions Surrounding It/ قصيدة البردة وما دار حولها من الشروح والتأليفات - Alhajj Ebrahim, Abdullah Omar; Al-Zahranmi, Mohammed Jarallah (Ijaz Arabi Journal of Arabic Learning, 2025)
The Arabic literary heritage is rich and full of stories, tales, anecdotes, poems, and everything that appeals to human taste. This heritage includes many famous and remarkable poems. Classical literary collections—such as Hamasat (an enthusiastic collection of poems), Amali (dictations), and others—contain many of these poems and literature. Some of these poems have received significant attention from scholars who have studied and analyzed them. Among the most famous is the poem "Al-Burda" (Banat Su'ad) by Ka'b ibn Zuhayr, which he recited before the Prophet Muhammad when he came to seek forgiveness after the decree to execute him. This poem sparked a great wave of poetry and prose writing—ranging from explanations and grammatical analyses to responses, adaptations, and various poetic forms such as takhmis (quintains), tasbi‘ (heptastichs), tathmin (octaves), and tatsi‘ (nonets). This study aims to present a bibliography that includes all the works written about the poem "Banat Su'ad" and to make it available to researchers for examination, study, and publication. The methods used are literature and content analysis. Due to the large amount of material the researcher has collected, the researcher limits himself to direct comments, postponing works of unknown authorship, poetic adaptations (takhmis, imitations), and contemporary studies to a separate research project. Result: commentaries on Bānt Su'ād include the commentary of Muhammad ibn Habib, the commentary of Imam Abu al-Abbas Tha'lab, the commentary of Ibn Duraid, the commentary on Bānt Su'ād by Ali ibn Muhammad al-Busti, the commentary of Abu al-Hasan Ali ibn Ahmad al-Wahidi, the commentary on Bānt Su'ād by Abu al-Tahir al-Salfi al-Jarwani, the commentary of Abu al-Qasim al-Suhayli, the commentary on Bānt Su'ād by Muhammad ibn Amir Ikhwan al-Salihi, and Dhakr al-Ma'ād fi Mu'āradah Bānt Su'ād by al-Busiri and the commentaries based on them, including the commentary of Ibn Sayyid al-Nas, entitled 'Adda al-Ma'ād fi al-A'rūd al-Bānt Su'ād, the summary of Bānt Su'ād by Khatib 'Ayn al-Zaytoun, the prosody of Bānt Su'ād by al-Safadi, and Bulugh al-Murad on the weight of Bānt Su'ād by Ibn Nabatah, and many others. Some commentaries were printed in the past and need to be re-verified and compared with other commentaries, including the commentary on Bānt Su'ād by Ibn 'Ashur and the commentary on Bānt Su'ād by Muwaffaq al-Din al-Baghdadi, all of which require scholarly verification. There are dozens of manuscripts of quintets, oppositions, and compositions written on Banat Suad, all of which are manuscripts.